THE ACCEPTANCE OF SUSTAINABLE FOOD CONCEPT: A QUALITATIVE EXPLORATION IN STENDEN UNIVERSITY HOTEL, THE NETHERLANDS - Han, Sia Tjun; Wahyudi, Wahyuniwati (Jurnal Manajemen dan Kewirausahaan, 2017)
As customers concern more about the environment, sustainable food demands, which are locally produced, organic, seasonal, and vegetarian or semi-vegetarian, are increasing. Besides, Theory of Planned Behavior (TPB) explains that behavior is guided by intentions with the factors of attitude, subjective norm, and perceived behavioral control to predict food choices; food purchasing habits and intake; and attitudes and preferences. Therefore, the research purpose is to examine customers’ acceptance of The Netherlands restaurant implementing sustainable food concept using TPB. Data analysis of 10 semi structured interviews shows that the customers of Restaurant NL are more likely guided by external factors of subjective norms: work related dine-in; others’ encouragement to eat more healthy and more responsibly, as the intentions are to have sustainable benefits.